Impact of diabetes mellitus on the relationship between a Poiseuille-based index and fractional flow reserve in intermediate coronary lesions. Issue 7 (November 2021) - Zuo, Wenjie; Zhang, Xiaoguo; Carvalho, Abdlay; Qu, Yangyang; Ji, Zhenjun; Tao, Zaixiao; Ma, Genshan
Abstract : Background: The ratio of lesion length (LL) to the fourth power of minimal lumen diameter (MLD) (LL/MLD 4 ) is a Poiseuille-based index with good diagnostic accuracy for the detection of coronary lesions with abnormal fractional flow reserve (FFR). We aimed to evaluate the impact of diabetes mellitus (DM) on its performance in intermediate coronary stenoses. Methods: We performed quantitative coronary angiography and simultaneous FFR measurement in 324 patients (234 non-DM and 90 DM) with 335 coronary lesions. The area under the receiver-operating characteristic curve (AUC) for angiographic parameters was determined, using an FFR value ⩽0.80 to indicate the physiological significance of coronary stenoses. Results: In the non-DM group, FFR was significantly related to percent diameter stenosis (%DS) ( R = −0.238) and LL/MLD 4 ratio ( R = −0.301; P < 0.001 for both). In the DM group, there was no correlation between %DS and FFR, whereas a close-to-threshold correlation was observed for the LL/MLD 4 ratio ( R = −0.205; P = 0.048). The AUC of LL/MLD 4 ratio was significantly different between non-diabetic and diabetic subjects (0.738 vs. 0.540; P = 0.024). Moreover, the LL/MLD 4 ratio showed higher AUCs than %DS (0.738 vs. 0.635; P = 0.017) and LL (0.738 vs. 0.634; P = 0.024) in non-diabetic population but this superiority did not exist in diabetic population. Conclusion: We showed good diagnostic accuracy of LL/MLD 4 ratio for identifying ischemic lesions in patients without DM. However, there was an impaired performance in diabetic patients and thus FFR measurement is essential to determine their hemodynamic status.